1980
DOI: 10.1136/bjo.64.6.385
|View full text |Cite
|
Sign up to set email alerts
|

Xenon arc photocoagulation for the treatment of diabetic maculopathy. Interim report of a multicentre controlled clinical study.

Abstract: SUMMARY The results of a randomised controlled clinical study in the treatment of diabetic maculopathy are reported. Ninety-nine patients with two similarly affected eyes had one-chosen by random procedure-treated, while the other was left as an untreated control. Visual acuity was maintained in the treated eyes, while it deteriorated in the untreated eyes, reaching over 2 lines difference after 4 years. The difference in deterioration was significantly less in treated than in untreated eyes at each assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Screening of 178 black patients attending the diabetic clinic of the University Hospital of the West Indies, Kingston, described severe visual loss (~< 2/ 60) in 11% of eyes, maculopathy being responsible for 53% of these cases [5]. Photocoagulation has been recommended for diabetic maculopathy [1,3,7,9], however the detection of treatable cases can be difficult as patients often present with advanced maculopathy with irreversible visual loss. This study was designed to assess the prevalance and risk factors for maculopathy in an unselected sample of black Jamaicans with maturity onset diabetes (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Screening of 178 black patients attending the diabetic clinic of the University Hospital of the West Indies, Kingston, described severe visual loss (~< 2/ 60) in 11% of eyes, maculopathy being responsible for 53% of these cases [5]. Photocoagulation has been recommended for diabetic maculopathy [1,3,7,9], however the detection of treatable cases can be difficult as patients often present with advanced maculopathy with irreversible visual loss. This study was designed to assess the prevalance and risk factors for maculopathy in an unselected sample of black Jamaicans with maturity onset diabetes (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…[ 7 8 ] Early efforts at treating macular edema with laser before significant visual loss occurs yielded favorable results. The literature review of similar photocoagulation studies in DME such as Olk et al .,[ 12 13 ] the British multicenter study group,[ 14 ] Blankenship[ 15 ] and ETDRS research group,[ 5 ] has shown that macular photocoagulation is effective in treating macular edema and in stabilizing vision. [ 7 ] ETDRS showed that photocoagulation decreased persistent macular edema and significant visual loss by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that intra vitreal Avastin helps decrease macular oedema even when other treatments have failed. (21) In another land mark study, the Pan American collaborative study group (PANCORES) studied the effect of primary intravitreal Avastin in diffuse macular oedema. At the end of two-year follow-up, the number of mean injections required was 5.8 with stability being documented in terms of BCVA and OCT at the end of 24 months.…”
Section: Resultsmentioning
confidence: 99%